Towards promising antimicrobial alternatives: The future of bacteriophage research and development in Saudi Arabia. Issue 12 (December 2022) - Alsaadi, Ahlam; Imam, Mohammed; Alghamdi, Abdulrahman A.; Alghoribi, Majed F.
Abstract: The escalating threat of antibiotic-resistant pathogens resulting from the rapid emergence of antimicrobial resistance (AMR) is a significant health and economic concern worldwide, exacerbated by the misuse of antibiotics in both humans and livestock. This has led to critical challenges when treating infections by multi-drug resistant (MDR) pathogens, which often display high mortality and morbidity rates. An international action plan and multisectoral cooperative approach are therefore needed to combat and halt AMR dissemination. Critical to these efforts are enhanced research programs aimed at identifying new antimicrobial agents, as well as the use of advanced biotechnology tools to develop alternative antimicrobial approaches. Bacteriophages (phages)—viruses that infect and kill bacteria—represent a promising tool for combatting the global threat of antibiotic-resistant pathogens. Phages and their potential applications have been extensively studied in Europe and the United States (US) for decades. However, although health authorities in the Gulf Health Council (GHC), including Saudi Arabia, have developed an action plan to combat AMR, phage research in the Middle East has lagged behind global scientific efforts. Thus, there is still a paucity of phage-related studies in this region, including those focused on therapeutic applications, clinical trials, biotechnology, and biocontrol. This article highlights the importance of bacteriophage research and development and discusses the potential implementation of phage-based therapies in Saudi Arabia.